CYP2U1 mutations in two Iranian patients with activity induced dystonia, motor regression and spastic paraplegia. (September 2016) - Kariminejad, A.; Schöls, L.; Schüle, R.; Tonekaboni, S.H.; Abolhassani, A.; Fadaee, M.; Rosti, R.O.; Gleeson, J.G.
Abstract: Hereditary spastic paraplegia (HSP) is a heterogeneous condition characterized by progressive spasticity and weakness in the lower limbs. It is divided into two major groups, complicated and uncomplicated, based on the presence of additional features such as intellectual disability, ataxia, seizures, peripheral neuropathy and visual problems. SPG56 is an autosomal recessive form of HSP with complicated and uncomplicated manifestations, complicated being more common. CYP2U1 gene mutations have been identified as responsible for SPG56. Intellectual disability, dystonia, subclinical sensory motor neuropathy, pigmentary degenerative maculopathy, thin corpus callosum and periventricular white-matter hyperintensities were additional features noted in previous cases of SPG56. Here we identified two novel mutations in CYP2U1 in two unrelated patients by whole exome sequencing. Both patients had complicated HSP with activity-induced dystonia, suggesting dystonia as an additional finding in SPG56. Two out of 14 previously reported patients had dystonia, and the addition of our patients suggests dystonia in a quarter of SPG56 patients. Developmental regression has not been reported in SPG56 patients so far but both of our patients developed motor regression in infancy.